Teaching Justice-Oriented Picturebooks Through Collaborative Discussion and ‘Slow Looking’: Implications for Initial Teacher Education Settings - Angie Zapata; Sarah Reid; Mary Adu-Gyamfi (Education Sciences, 2025)
Picturebooks have a long history as literature for literacy learning in initial teacher education (ITE) settings. Yet, the practice of “using” picturebooks solely to teach isolated skills becomes more alarming as pre-service teachers encounter classroom picturebook instruction that features diverse racial, linguistic, or ethnic communities as “plugged” into scripted curriculum without opportunities for students to respond to the socio-cultural portrayals encountered. Guidance for ITE programs is needed to ensure that the aesthetic and sociopolitical features of picturebooks are not only considered but deeply taught to pre-service teachers. Drawing from a qualitative analysis of a fifth-grade reader engaging with a picturebook featuring a character with a similar phenotype across ten days, an inductive and iterative process of data analysis identified salient moments of collaborative discussions and the ‘slow looking’ approaches she used to interact with justice-oriented picturebooks. Our findings highlight the visual, material, and multimodal ways these texts serve as mentor resources for writing and drawing, while also acting as identity-affirming texts. To conclude, we offer essential implications for ITE settings, instructors, and their students by unpacking the significance of instruction that matters most for supporting pre-service teachers as curators of justice-oriented picturebooks.